Influence of Blanching on the Gene Expression Profile of Phenylpropanoid, Flavonoid and Vitamin Biosynthesis, and Their Accumulation in Oenanthe javanica - Sunjeet Kumar; Xinfang Huang; Qun Ji; Abdul Qayyum; Kai Zhou; Weidong Ke; Honglian Zhu; Guopeng Zhu (MDPI AG, 2022)
Field blanching is a process used in agriculture to obtain sweet, delicious, and tender stems of water dropwort by obstructing sunlight. The nutritional and transcriptomic profiling of blanched water dropwort has been investigated in our previous studies. However, the effect of blanching on the production of secondary metabolites and different vitamins in water dropwort has not been investigated at the transcriptomic level. This study explored the transcriptomic variations in the phenylpropanoid biosynthesis, flavonoid biosynthesis, and different vitamin biosynthesis pathways under different blanching periods in the water dropwort stems (pre-blanching, mid-blanching, post-blanching, and control). The results show that polyphenol and flavonoid contents decreased; however, the contents of vitamins (A, B1, B2, and C) and antioxidant activity increased significantly after blanching. Furthermore, the Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis of blanched water dropwort showed the downregulation of many important genes involved in phenylpropanoid and flavonoid biosynthesis pathways, and the downregulation of these genes might be the reason for the reduction in polyphenol and flavonoid contents. We also examined and highlighted the genes involved in the higher vitamin content, antioxidant activity, pale color, tenderness, and sweetness of the blanched stem of water dropwort. In conclusion, the present study explored the role of phenylpropanoid and vitamin biosynthesis, and it will provide a basis for future investigation and application in the blanch cultivation of water dropwort.